Analytical Study of Household Environmental Sanitation and Food Sanitation With Incidence of Diarrhea - Adhyatma A; Andi Alim; Nur Inah (Jurnal Publikasi Kesehatan Masyarakat Indonesia, 2022)
Bad environmental conditions are one of the factors increasing the incidence of diarrhea. Where environmental health includes several factors including housing, sewage disposal, clean water supply, and waste water drainage. South Panggilian Environment, South Benteng Sub-District, Benteng District, and Selayar Islands Regency, is an area that still has poor environmental sanitation or does not require health standards. In this case, especially the problem of sewerage that still does not follow health sanitation requirements. If left unchecked, it will become one of the risk factors for increasing disease, especially diarrheal diseases. The purpose of this study was to determine the relationship between sanitation and the incidence of diarrhea in the South Panggilian Environment, South Benteng SubDistrict, Benteng District, and Selayar Islands Regency. This research is a type of research in the form of an observational survey with a cross-sectional approach with a population of 238 families. To determine the sample size, the slovin formula was used to obtain a total sample of 77 families. This research was conducted in October - November 2021. In collecting data using a questionnaire to the selected respondents, the data was then processed and displayed in tabular form. Based on the results of the study, it was found that there was a relationship between clean water facilities (p-value = 0.02), drinking water facilities (p-value = 0.00), feces/latrine disposal facilities (p-value = 0.00), sewage facilities wastewater (p-value=0.02), waste disposal facilities (p-value=0.00) and food sanitation (p-value=0.00) with the incidence of diarrhea. Based on the results of the study, it was suggested that the respondents make a means for disposing of wastewater at home and outside the home so that they do not interfere with each other, causing a very pungent odor seen from flood-prone areas.